Anemia In Pregnancy With Stunting In Gayam Village District Gurah Kediri: Anemia Pada Kehamilan Dengan Kejadian Stunting Di Desa Gayam Kecamatan Gurah Kabupaten Kediri - Rahayu, Dewi Taurisiawati (Jurnal Kebidanan Midwiferia, 2021)
The nutritional status and health of the mother during pre-pregnancy, pregnancy, and during breastfeeding was very critical periods for children's growth and development. The aim of this research was to determine the relationship between anemia during pregnancy and the incidence of stunting. The method used in this research was observational correlational analytic, which looking for the relationship between two independent and dependent variables used a cohort-retrospective approach, with the independent variable anemia during pregnancy and the dependent variable the incidence of stunting. The research was conducted from 2 July – 29 August 2020 in Gayam Village, Kediri Distric used MCH book instrument. Total population was 512 toddlers with judgement sampling technique as many as 88 toddlers consisted of 38 stunting and 50 non-stunting toddlers. Analysis used the Spearman Rho with the results of the Spearman value showed that total of 66 toddlers, 4 (6.1%) of stunting toddlers were found with no history of anemia, 13 (19.7%) of stunting toddlers with a history of mild anemia and 5 (7.6%) of stunting toddlers with a history of moderate anemia. Spearman rho test results p value = 0.000. This mean that the p value <α = 0.05, because the p-value <α, H1 accepted, that there was a relationship between a history of anemia during pregnancy and the incidence of stunting on toddlers. Anemia during pregnancy was very risky for the development of fetus and the development of baby that will beb born can caused stunting.